Ultrathin polymer membrane for improved hole extraction and ion blocking in perovskite solar cells - Lina Shen; Peiquan Song; Kui Jiang; Lingfang Zheng; Jianhang Qiu; Fangyao Li; Yu Huang; Jinxin Yang; Chengbo Tian; Alex. K.-Y. Jen; Liqiang Xie; Zhanhua Wei (Nature Communications)
Abstract Highly efficient perovskite solar cells (PSCs) in the n-i-p structure have demonstrated limited operational lifetimes, primarily due to the layer-to-layer ion diffusion in the perovskite/doped hole-transport layer (HTL) heterojunction, leading to conductivity drop in HTL and component loss in perovskite. Herein, we introduce an ultrathin (~7 nm) p-type polymeric interlayer (D18) with excellent ion-blocking ability between perovskite and HTL to address these issues. The ultrathin D18 interlayer effectively inhibits the layer-to-layer diffusion of lithium, methylammonium, formamidium, and iodide ions. Additionally, D18 improves the energy-level alignment at the perovskite/HTL interface and facilitates efficient hole extraction. The resulting PSCs achieve efficiencies of 26.39 (certified 26.17) and 25.02% with aperture areas of 0.12 and 1.00 square centimeters, respectively. Remarkably, the devices retain 95.4% of the initial efficiency after 1100 hours of operation in maximum power point tracking, representing significant stability advancements for high-efficiency n-i-p PSCs.